Straightness knee butterfly kick makes more lactate acid during butterfly swimming. A case study with a high-level swimmer - Ide, T.; Takise, S.; Yoshimura, Y.; Kawamoto, K.; Schaffer, S.; Johnson, W. F.; Kawakami, T. (International Journal of Swimming Kinetics, 2012)
The technique of straightness knee bending kick makes more lactate. Straightness knee butterfly kick increase one stroke velocity, Distance per stroke and max speed. We compared subject's 2005 stroke to his 2009 stroke, we found that the extent to the straightness of his butterfly kick improved from 39% to 55% (of >170 degrees knee-bending). The straight Fly kick increase lactate acid made 6.7mmol/L. The subject performed 25 meter butterfly where the first 15 meters swam under water butterfly kick and the remaining 10 meters all out butterfly stroke. Swimming Speed Mater (Vine, VMS-003, AC100V, 1/500sec, 0.2mm/pulse) generated the data by an attached wire with movement place. The wire then exports the analogue signals and RS232C signals. These signals calculated are then examined using Microsoft Windows Excel and a Wilcoxon Signed Ranked Test. While swimming, the subjects were monitored from the side using an underwater video camera at a sampling frequency of 60Hz (Underwater monitor system 2, YAMAHA, Shizuoka, Japan). The subject strokes angle of degree was analyzed with DartTrainer in regards to the bending of the knee and upper body movement. The subject lactate acid measured by Lactate Pro LT-1710 (Arkray, 5 mmol/L Kyoto, Japan) The subject employed Swimming Speed Mater showed the max speed was 2.5m/sec (2005) to 2.7m/sec (2009) at the second kick phase respectively. The distance per stroke (DPS) results were different resulting in a 2.204m±0.131 for 2009 and 1.894m±0.062 for 2005 (DPS (m) Wilcoxon.: p=0.006061, 1 stroke (velocity) Wilcoxon.: p=0.7748) and Dart Trainer showed the straight knee +170 degree was 55% use of straight knee kick for 2009 and 39% for 2005, in the one stroke. The Lactate pro showed lactate acid, straight knee kick 6.7mmol/L, bending knee kick 4.3mmol/L. After 30 second, subject could not hold his straightness knee butterfly kick at the lactate test. The lactate test showed same results as 4 international swimmers, include Japanese national team swimmers and Canadian national swimmer. The straightness Knee kick technique needs keep low lactate acid, increased 1 stroke velocity, max speed, and distance per stroke. This suggests that subject needs train to keep straight knee butterfly kick second half of 100 meter butterfly.